¿Puede el jurista discurrir como un científico social? (Posibilidades e imposibilidades del derecho como «ciencia» social) - Haba, Enrique P. (Universidad de Costa Rica, 2022)
Knowledge produced in nearly all Social Sciences (Sociology, Political Science,Linguistics, etc.) is almost useless or useless at all —except for scientists themselvesor for their own publishing-market. On the contrary, legal precepts and the doctrineapplied to them bring about a large variety of real effects on the concrete life of allpeople. The price paid for that efficiency is having law built as a web of discourseswithout genuine scientific rigor.